Detection, Clinical Features, and Laboratory Markers of H.pylori Infection in Individuals attended Kosti Teaching Hospital, Sudan - Azoz, Mohammed Eltoum; Almugadam, Babiker Saad; Ibrahim, Omer Mohammed Ali; Ahmed, Yousif Mousa Alobaid; Tayeb, Amna Ahmed Al; Eshagg, Noor Hussin; Hassan, Roaa Azhari (Biomedical and Biotechnology Research Journal, 2022)
Background: Helicobacter pylori infections are associated with significant morbidity. The study intended to screen H. pylori among symptomatic patients and assess the performance of anti-H. pylori immunoglobulin G (IgG) test compared to stool Ag test as well as to investigate some clinical and hematology findings in H. pylori-seropositive persons. Methods: One hundred individuals with the clinical suspicion of infection by H. pylori and 100 control subjects matched for gender (χ2 = 0.026, P = 0.873) and age groups (χ2 = 5.303, P = 0.151) were recruited. Clinical assessment, endoscopy, anti-H. pylori IgG test, and stool for cagA Ag were performed to investigate H. pylori infection. White blood cells, red blood cells (RBCs), hemoglobin (Hb), and mean corpuscular hemoglobin (MCH) were also analyzed. Results: Vomiting and hematemesis were reported in 44% and 8% of the study group, respectively. Whereas, nausea, epigastric pain, and weight loss were observed in all (100%). Notably, gastritis and duodenal ulcer were detected in 100% and 80% of cases, respectively. Based on Immunochromatographic test (ICT), 75% and 78% of the study group were positive for anti-H. pylori Ab and cagA Ag of H. pylori, respectively. The odd of reported a positive result for H. pylori was less likely in females than males as determined by anti-H. pylori (odds ratio [OR]: 0.529, 95% confidence interval [CI]: 0.142–1.970, P: 0.343) and stool cagA Ag test (OR: 0.364, 95% CI: 0.087–1.532, P: 0.168). Compared to the cagA Ag test, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of anti-H. pylori test were 77.2%, 85.3%, 78.7%, 84.1%, and 81.9%, respectively. Interestingly, RBCs count, MCH, and Hb were significantly higher in the control compared to study cases, P < 0.05. Conclusions: Our results highlight the epidemiology of into H. pylori, assess the performance of anti H. pylori test compared to cagA Ag test, and demonstrate the direct link between some hematologic indices and H. pylori. Further studies are necessary to verify these findings.